OWN GOAL: COMPARISON OF MEDIAMETAPHORS IN UKRAINIAN AND POLISH JOURNALISM - Tetiana Faichuk; Іlona Myroshnichenko; Iryna Stohnii; Alla Vilchynska (Інтегровані комунікації)
Metaphorical expressions play an important role in modern media language, especially in the headlines of articles. The article presents a comparative analysis of the use of the expressions "гра в одні ворота" / "grać do jednej bramki" and "гол у свої ворота" / "strzał do własnej bramki" in Ukrainian and Polish media.